How deadly is a fracture distal to the hip in the elderly? An observational cohort study of 11,799 femoral fractures in the Swedish Fracture Register - Wolf, Olof; Mukka, Sebastian; Ekelund, Jan; Möller, Michael; Hailer, Nils P (Acta Orthopaedica, 2020)
Background and purpose — Unlike hip fractures, diaphyseal and distal femoral fractures in elderly patients have not been widely studied. We investigated the demographics, comorbidities and mortality of patients with femoral fractures at any anatomical level with a focus on early mortality. Patients and methods — We analyzed 11,799 patients ≥ 65 years with a femoral fracture registered in the Swedish Fracture Register from 2011 to 2014. The cohort was matched with the National Patient Register to obtain data on comorbidities classified according to the Charlson Comorbidity Index (CCI). Generalized linear models were fitted to estimate the adjusted relative risk of mortality. Results — Mean age of the cohort was 83 years and 69% were women. Patients with distal femoral fractures had the lowest degree of comorbidity, with 9% having a CCI of ≥ 3 compared with 14% among those with proximal and 16% among those with diaphyseal fractures. Unadjusted 90-day mortalities were 13% (95% CI 9.4–16) after fractures in the distal, 13% (CI 10–16) in the diaphyseal, and 15% (CI 14–15) in the proximal segment. The adjusted relative risk for 90-day mortality was 1.1 (CI 0.86–1.4) for patients with distal and 0.97 (CI 0.76–1.2) for patients with diaphyseal femoral fractures when compared with patients with hip fractures. Interpretation — Elderly patients with femoral fractures distal to the hip may have similar adjusted early mortality risks to those with hip fractures. There is a need for larger, preferably prospective, studies investigating the effect of rapid pathways and geriatric co-management for patients with diaphyseal and distal femoral fractures.